Mortalidade por causa em bombeiros e policiais militares do Espírito Santo - Teixeira, Elaine Mélo (2023)
Work-related stress and exposure to hazardous or unhealthy substances is a risk factor for developing diseases. Some professionals are more susceptible to stress and occupational exposure and unhealthy conditions due to the nature of work, which can affect health balance and eventual reduction in the longevity. To investigate the leading causes of death in a population of Brazilian male military police officers and firefighters over three decades, comparing their mortality with the general population. A retrospective study was carried out analyzing the death certificates of male military police officers and firefighters from the state of Espírito Santo, a state in the Southeast of Brazil, from 1988 to 2019. Women were not included due to reduced number among officers. The underlying cause of death was considered the main cause of death. Deaths were analyzed according to age, year of occurrence, cause of death, skin color and decade of death. The mortality rate was estimated by decades (1990 to 1999; 2000 to 2009 and 2010 to 2019) and the Standardized Mortality Rate (SMR) for the three main causes compared with the local and national population mortality. Variables were characterized by descriptive analysis and categorical variables was analyzed by Chi-square test. The Prais-Winsten regression model was used to analyze the temporal trend in mortality, being the dependent variable the absolute frequency of deaths and the independent variable the year of death. 2198 deaths were observed among officers, with an average death age of 59 ± 18.5 years. The main causes of death were diseases of the circulatory system (32%), external causes (26%) and neoplasms (15%). Diseases of the circulatory system deaths were the most prevalent in police officers and firefighters of all skin colors, especially among black officers. When compared with the general population, deceased officers presented a higher mortality from circulatory system diseases and external causes, over two decades and from neoplasms, in one decade. We observed a premature age of death among police officers and firefighters as well as a high prevalence of deaths from circulatory diseases, external causes, and neoplasms compared to the general population, highlighting the need for preventative actions and health monitoring among these professionals.